2020
DOI: 10.47162/rjme.61.2.22
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid and vitamin B complex slow down the changes in mice diabetic cardiomyopathy

Abstract: This is an open-access article distributed under the terms of a Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International Public License, which permits unrestricted use, adaptation, distribution and reproduction in any medium, non-commercially, provided the new creations are licensed under identical terms as the original work and the original work is properly cited. ORIGINAL PAPER Alpha-lipoic acid and vitamin B complex slow down the changes in mice diabetic cardiomyopathy GEORGICĂ COSTINEL TÂRTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…B vitamins are usually used as antioxidants because of their excellent antioxidant activities. α-LA is a coenzyme that belongs to the vitamin B family that exists in the mitochondria [19]. Some researchers have demonstrated that α-LA (often called a super antioxidant) reduces the amount of free radicals or ROS in the body, for example, NO, hydrogen peroxide and hydroxyl radical [20].…”
Section: Introductionmentioning
confidence: 99%
“…B vitamins are usually used as antioxidants because of their excellent antioxidant activities. α-LA is a coenzyme that belongs to the vitamin B family that exists in the mitochondria [19]. Some researchers have demonstrated that α-LA (often called a super antioxidant) reduces the amount of free radicals or ROS in the body, for example, NO, hydrogen peroxide and hydroxyl radical [20].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding induction and assessment of diabetes mellitus and therapeutic protocols in mice, diabetes was induced by a single intraperitoneal injection and the administration of 150 mg streptozotocin/kg body weight, between 8 and 10 weeks of life, as in two of our previous studies [58,59]. Diabetes mellitus was diagnosed according to the criteria of the American Diabetes Association (ADA) [60].…”
Section: Animalsmentioning
confidence: 99%
“…In addition, it is also obtained from plant and animal sources and can also be given as a dietary supplement ( Shay et al, 2009 ). A growing body of preclinical and clinical evidence shows that ALA effectively improves glucose homeostasis and lipid profile in both T1DM and T2DM and also plays a cardioprotective role against development and/or progression of DCM through its potent multifunctional antioxidant property ( Strödter et al, 1995 ; Midaoui et al, 2003 ; Li et al, 2009 ; Lee et al, 2012; Li et al, 2012 ; Lee et al, 2017 ; Akbari et al, 2018 ; Târtea et al, 2020 ). It is also beneficial in clinical and experimental models of other diabetic complications such as diabetic peripheral neuropathy ( Lee T. H. et al, 2012 ; Ziegler et al, 2016 ; Verma, 2018 ), diabetic nephropathy ( Chang et al, 2007 ; Lee et al, 2009 ) and gestational diabetes mellitus ( Aslfalah et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%